The role of technology in promoting relevance research quality and access to MSTE (2015)
The enhanced use of ICT in teaching and research helps to improve academic productivity, thus enabling researchers to spend more time on research. ICT opens up access to education by removing many of the temporal and spatial constraints to information and knowledge. Furthermore, the availability of learning materials-based on ICT can greatly improve learning resources. Efficient use of ICT allows students to develop the kinds of skills and competences that many educational reform panels have viewed as essential. Basic skills such as arithmetic can be mastered with computer- aided drill and practice, while writing skills can be developed with word processing, which makes writing and revising easier. A deep understanding of complex scientific concepts, in mathematics and science, particularly where experiments are not feasible can be gained through computer simulations. The use of these technologies for learning may establish familiarity with technologies that are increasingly needed by individuals in a technology driven society. In the light of the above, this paper presents discussion on the role of ICT in promoting research relevance, and as well discusses how access to technology can improve Mathematics, Science and Technology Education.